Impelementasi Cerita Rakyat melalui Mata Kuliah Pendidikan Seni Tari Usia Dini untuk Meningkatkan Kreativitas Pada Mahasiswa PG-PAUD FKIP UNSRI - Hasmalena Hasmalena; Mahyumi Rantina (LPPM Universitas Pahlawan Tuanku Tambusai, 2017)
The purpose of this research is to improve the creativity students of PG-PAUD FKIP Unsri. The type of research used is action research with Kemmis and Taggart model conducted 4 meetings. Subjects in this study as many as 40 people consisting of 38 women and 2 men. Data were collected by observation, interview, and documentation by using qualitative descriptive data analysis technique. The results showed that with folklore in dance courses can increase creativity, as evidenced by the observations made have achieved 75% success indicator. In the 1st cycle of the meeting 1 aspect smoothness is in category 63,33%, flexibility is in category 58,33%, orginality are in category 54,16%, elaborate is in category 55,83%, systematic is in category 57,5%. Second in the first cycle of the second meeting, the smoothness of 66.66%, the flexibility aspect of 71.66%, orginality aspect of 74.16%, elaborate 72.5%, systematic by 69.16%. Third on cycle 2 of meeting 1 on the smoothness aspect of 79,16%, variable 75%, orginalitas 77%, elaborate by 78%, systematic equal to 83%. Fourth in cycle 2 of meeting 2, smoothness aspect 80%, flexibility 80,83%, orginality 80,83%, elaborate 84,16%, and systematic aspect equal to 85%. The results of this study show that with folklore in the art of dance can improve creativity in students PG-PAUD FKIP Unsri.